2021
DOI: 10.34117/bjdv7n1-067
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos Estruturais E Diversidade Arbórea Em Fragmento Florestal Urbano No Oeste Paranaense / Structural Aspects and Arbory Diversity in Urban Forest Fragment in West Paranaense

Abstract: Este estudo buscou avaliar diversidade taxonômica e a variação estrutural do componente arbóreo através do levantamento fitossociológico em um remanescente de Floresta Estacional Semidecidual (FES) no Oeste do Paraná. Foram amostradas 167 árvores de 43 espécies pertencentes a 38 gêneros e 19 famílias botânicas. A diversidade de 3,24 nats/ind. e a equalibidade de 0,85 indicam elevada heterogeneidade florística. Fabaceae e Meliaceae foram as famílias com maior número de espécies e indivíduos na floresta sendo Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…In recent years, relevant floristic survey work has been carried out in the Atlantic Forest in several states, Joly et al (2012) in São Paulo, Machado et al (2012) in Alagoas, Zama et al (2012) in Paraná, França and Stehmann (2013) in Minas Gerais, Matos et al (2013) in Sergipe, Lorenzoni et al (2014) in Espírito Santo, Alves et al (2015) in Bahia, Ferrarese et al (2016) in Rio Grande do Sul, Silva (2017) in Rio de Janeiro. Some research was even managed in the same forestry formation as this work, at FES, Naves and Berg (2012), Figueiredo et al (2013), Pinto et al (2013), Meira Junior et al (2015 and Moura et al (2022) in Minas Gerais, Nogueira and Marchiori (2018) in São Paulo, Almeida (2013), Garcia (2015), Aguiar (2015), Garcia and Romagnolo (2015), Estevan et al (2016), Bald et al (2021) Lisboa et al (2021) in Paraná, in addition to Franco (2017), Garcia et al (2017), Zeidan and Ferreira (2020) carried out floristic survey studies in Maringá-PR; such studies made an important contribution to biogeography. Franco (2017) in his study considered the Mimosoideae, the second largest subfamily of Leguminosae.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In recent years, relevant floristic survey work has been carried out in the Atlantic Forest in several states, Joly et al (2012) in São Paulo, Machado et al (2012) in Alagoas, Zama et al (2012) in Paraná, França and Stehmann (2013) in Minas Gerais, Matos et al (2013) in Sergipe, Lorenzoni et al (2014) in Espírito Santo, Alves et al (2015) in Bahia, Ferrarese et al (2016) in Rio Grande do Sul, Silva (2017) in Rio de Janeiro. Some research was even managed in the same forestry formation as this work, at FES, Naves and Berg (2012), Figueiredo et al (2013), Pinto et al (2013), Meira Junior et al (2015 and Moura et al (2022) in Minas Gerais, Nogueira and Marchiori (2018) in São Paulo, Almeida (2013), Garcia (2015), Aguiar (2015), Garcia and Romagnolo (2015), Estevan et al (2016), Bald et al (2021) Lisboa et al (2021) in Paraná, in addition to Franco (2017), Garcia et al (2017), Zeidan and Ferreira (2020) carried out floristic survey studies in Maringá-PR; such studies made an important contribution to biogeography. Franco (2017) in his study considered the Mimosoideae, the second largest subfamily of Leguminosae.…”
Section: Resultsmentioning
confidence: 84%
“…The sample plots vary in quantity, size and shape, and are used in addition to floristic surveys for phytosociological studies and other quantitative and structural assessments of the environment (OLIVEIRA, 1998;AGUIAR, 2003;JOLY, 2012;NAVES, 2012;ZAMA, 2012;ALMEIDA, 2013;DE FIGUEIREDO et al, 2013;PINTO, 2013;SCHLICKMANN et al, 2016;SILVA, 2017;BALD et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many resemblances in species composition exist when compared with other studies in nearby areas of Seasonal Semideciduous Forest [70,71,74] and transitional areas between Semideciduous and Mixed Forests [72,73,78] (Appendix 2); however, there are differences in the structure of the communities, mainly in the species that present the highest abundances and IV, probably due to the different conditions of each area, whether related to the environment or anthropic activities.…”
Section: Floristics and Phytosociologymentioning
confidence: 77%
“…Gris et al (2014) [70] analyzed fragments of Seasonal Semideciduous Forest under varying levels of disturbance and observed the predominance of Fabaceae, Meliaceae, Lauraceae, Myrtaceae and Moraceae. Likewise, Bald et al (2021) [71], in a forest remnant of Seasonal Semideciduous Forest, found Fabaceae, Meliaceae, Rutaceae, Lauraceae and Myrtaceae as the richest families. Souza et al (2019) [72] and Adenesky-Filho et al (2017) [73] found as predominant families Fabaceae, Myrtaceae, Lauraceae, Euphorbiaceae and Meliaceae, and Estevan et al (2016) [74] found Fabaceae, Meliaceae, Myrtaceae and Lauraceae.…”
Section: Floristics and Phytosociologymentioning
confidence: 96%
“…Isso pode ser evidenciado pela presença de clareiras (Figura 04 -A), resultantes da morte dos indivíduos ou da caducidade das espécies, bem como pela ocorrência de cortes seletivos, incêndios, estresse hídrico, fragmentação e efeitos de bordas (GANDOLFI, 2000). Em geral, a família Fabaceae se destaca como a mais diversa em espécies da FES no Paraná (COSTA et al, 2011;GORENSTEIN, 2016;DETTKE et al, 2018), assim como em outros estados brasileiros (PINHEIRO, 2000;BENVENUTI-FERREIRA;COELHO, 2009;SÁ et al, 2012).…”
Section: Materiais E Métodosunclassified